Use of 90% ethanol to decontaminate stethoscopes in resource limited settings - Bijendra Raj Raghubanshi; Supriya Sapkota; Arjab Adhikari; Aman Dutta; Utsuk Bhattarai; Rastriyata Bhandari (Antimicrobial Resistance and Infection Control, 2017)
Abstract Background In developing countries like Nepal, 90% ethanol is cheap and is available in most hospitals. The unavailability of isopropyl alcohol (IPA) in these settings led us to compare the efficacy between 90% ethanol and isopropyl alcohol pads in reducing the bacterial contamination of diaphragm of stethoscope. Methods A randomized blinded experimental study was carried out to determine the difference between cleaning stethoscopes with 90% ethanol and IPA. Cultures of diaphragm were taken before and after cleaning with one of the cleaning agent. Colony forming units (CFU) count and organism identification was done by a blinded investigator. CFU before and after cleaning were compared using Wilcoxon signed–rank test. Mann Whitney U test was used to compare the decrease in CFU count between the cleaning agents. Results About 30% of the stethoscopes harbored potential pathogens. Significant reduction in CFU was observed with both IPA (Wilcoxon signed–rank test, P value <0.001) and 90% ethanol (Wilcoxon signed–rank test, P value <0.001). Comparing median decrease in CFU between cleaning with IPA and with 90% ethanol, no significant difference was found (Mann Whitney U test; U = 1357, P value >0.05). Conclusions Both 90% ethanol and IPA are equally effective in decontaminating the diaphragm of stethoscope. Selection of agent should be done on the basis of cost and availability.